The juvenile hormone effect of the insecticidal principle from psychic nut, Jatropha curcas Linn. on cottton bolloworm, helicoverpa armigera (Hubn.) - Solsoloy, Aida D.; Morallo-Rejesus, B. (1992)
The insecticidal principle from psychic nut, Jatropha curcas, was extracted using two organic solvents (petroleum ether and chloroform). The crude oils derived were evaluated for their growth-regulating and chemosterilizing effect on Helicoverpa armigera.

The crude chloroform-extracted leaf oil incorporated in the diet of second instar H. armigera did not inhibit feeding and assimilation. However, it reduced biomass production as manifested by reduced growth rate. Moreover, larval develop-ment was inhibited resulting in a delay in molting. All the crude oils caused production of larval-pupal intermediates and abnormal adults. Based on the ID 50, the crude petroleum ether-extracted seed kernel and leaf oils were the most effective. The crude oils were insect growth regulators (IGRs).

Moreover, the crude oils from either the leaves or seed kernels extracted with petroleum ether had a partial chemosterilizing effect on H. armigera moths. The ovarioles of females from the larvae fed with the oil-treated diets showed morphological abnormalities. These results suggested that the crude oils were juvenile hormone mimics.
Keywords: Entomology; Infective larvae